2016
DOI: 10.3892/mmr.2016.5329
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the complementarity determining regions β-chain genomic rearrangement using high-throughput sequencing in periphery cytotoxic T lymphocytes of patients with chronic hepatitis B

Abstract: Cytotoxic T lymphocytes (CTLs) are important for the recognition of the hepatitis B virus (HBV), mediating immunoprotective mechanisms and determining the clinical outcome following HBV infection. CTLs recognize the invading virus via the T cell receptor (TCR). The aim of the current study was to investigate the variability of TCR in lymphocytes from patients with chronic hepatitis B and whether TCR genomic recombination is regulated by the current treatment strategies. Peripheral blood mononuclear cells (PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…By analysing the TCR repertoire of MAIT cells, we showed that peripheral blood MAIT cells in CHBV patients expressed higher levels of TRBV5.1 and TRBV11.2_TRBJ1.5 than intrasinusoidal MAIT cells. Recent reports have shown that TRBV5.1 and TRBV11 are highly associated with CHBV infection 27‐30 . Hence, the high levels of TRBV5.1 and TRBV11.2_TRBJ1.5 may explain why peripheral blood MAIT cells are more activated in response to CHBV infection than intrasinusoidal MAIT cells.…”
Section: Discussionmentioning
confidence: 99%
“…By analysing the TCR repertoire of MAIT cells, we showed that peripheral blood MAIT cells in CHBV patients expressed higher levels of TRBV5.1 and TRBV11.2_TRBJ1.5 than intrasinusoidal MAIT cells. Recent reports have shown that TRBV5.1 and TRBV11 are highly associated with CHBV infection 27‐30 . Hence, the high levels of TRBV5.1 and TRBV11.2_TRBJ1.5 may explain why peripheral blood MAIT cells are more activated in response to CHBV infection than intrasinusoidal MAIT cells.…”
Section: Discussionmentioning
confidence: 99%
“…TCR IR therefore serves as a "footprint" of immune status (Calis and Rosenberg, 2014). Emerging studies suggest that TCR IR participates in various liver diseases (including viral hepatitis, liver regeneration, hepatocellular carcinoma, primary sclerosing cholangitis, and alcoholic liver disease) (Chen et al, 2016;Huang et al, 2016;Liaskou et al, 2016;Jiang et al, 2018). In this study, we demonstrate the resetting of intrahepatic TCR IR in response to chronic liver injury, showing an intact characteristic of V, D, J, VJ, and VDJ segment usage and the distribution of CDR3 AA clonotypes during liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The TCR immune repertoire, which has been associated with various liver diseases (including chronic virus hepatitis, hepatocellular carcinoma, and primary biliary cirrhosis), is a potential tool to monitor intrahepatic immune status and the microenvironment. (20,(32)(33)(34) Accumulating studies indicate that PHx induces a series of inflammatory signaling cascades that interact to ensure complete LR. In this process, the immune response itself provides exact identification and has been associated with both hepatic parenchymal and nonparenchymal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%